FORMULATION OF BUSINESS DEVELOPMENT STRATEGIES USING IFE, EFE, IE, SWOT, AND QSPM MATRICES AT SEMASA COFFEE (COFFEE AND EATERY) - Sianturi, Ronauli; Arbainah, Siti; Widiarto, Ardian (Applied Accounting and Management Review (AAMAR), 2024)
This research is a descriptive study with a qualitative approach that aims to formulate alternative strategies that can be applied to Semasa Coffee. Data collection was conducted through observation, interviews, and quetionnaires. Data analysis using the IFE, EFE, IE, SWOT, and QSPM Matrices showed the results ofe the IFE weighted score of 2.924, EFE weighted score of 3.103 which means the company is in a fairly strong internal and external position in controlling strengths and weaknesses to face opportunities and threats. The results of the IE Matrix analysis show that the company's position is in cell II, namely "Grow and Build", so that appropriate strategies are intensive strategies and integration strategies. Based on SWOT analysis, 10 alternative strategies were developed for the company. Then using QSPM, the priority alternative strategy for Semasa Coffee is to continue to maintain product quality and flavour consistency, and innovate through cooperation with suppliers with a TAS value of 6.381.